2019
DOI: 10.1155/2019/9705327
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Property of Galectin-1 in a Murine Model of Allergic Airway Inflammation

Abstract: Galectin-1 (Gal-1) has immunomodulatory activities in various allergic inflammatory disorders, but its potential anti-inflammatory properties on allergic airway diseases have not been confirmed. We explored the pharmacological effects of Gal-1 on the progression of allergic airway inflammation and investigated the underlying mechanism. Female C57BL/6 mice were sensitized on day 0 and challenged with ovalbumin (OVA) on days 14-17 to establish an allergic airway inflammation model. In the challenge phase, a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Pharmacological interventions with recombinant Gal-1 protein plays an essential immunoregulatory role by inhibiting CD4 + T-cell effector functions in different pathologies J o u r n a l P r e -p r o o f such as Crohn's disease (Santucci et al, 2003), multiple sclerosis (Toscano et al, 2007) or asthma (Lv et al, 2019). Previous studies have shown that the interaction between Gal-1 and CD69 modulates Th17 effector cell differentiation and function (de la Fuente et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological interventions with recombinant Gal-1 protein plays an essential immunoregulatory role by inhibiting CD4 + T-cell effector functions in different pathologies J o u r n a l P r e -p r o o f such as Crohn's disease (Santucci et al, 2003), multiple sclerosis (Toscano et al, 2007) or asthma (Lv et al, 2019). Previous studies have shown that the interaction between Gal-1 and CD69 modulates Th17 effector cell differentiation and function (de la Fuente et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To date, these Gals have been found to regulate different cellular functions, including the interaction of galactoside ligands with different proteins in embryonic development, inflammation, immune response, metabolic disease, premRNA splicing, cell cycle, motility, survival, organ fibrosis, and cancer development (Figure 2) [9][10][11][12][13][14][15]. Gals are involved in cell proliferation, migration, anti-apoptosis, carbohydrates, proteins, lipid metabolism or nucleic acid synthesis, resistance to drug treatment, immune system or inflammation response, vessel generation, organ fibrogenesis, and resistance to death.…”
Section: Gal Functions In Cell Biologymentioning
confidence: 99%
“…To date, these Gals have been found to regulate different cellular functions, including the interaction of galactoside ligands with different proteins in embryonic development, inflammation, immune response, metabolic disease, premRNA splicing, cell cycle, motility, survival, organ fibrosis, and cancer development ( Figure 2 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Gal Functions In Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate Gal 1 as a potential therapeutic protein, Ly et al have shown that the recombinant Gal 1 protects from allergic asthma in a mouse model (22). The immunomodulatory effects in the allergic lung were correlated with the activation of the extracellular signal-regulated kinase signaling pathway and downregulation of endogenous Gal-1.…”
Section: Galectins -Soluble Glycoreceptors Recognizing Galactose-containing Moleculesmentioning
confidence: 99%